MODELLING AND SIMULATION OF AN MR BRAKE BASED ON TORQUE COMPENSATION (Journal of Transport System Engineering, 2024)
A new design for a repetitive compression magnetorheological (MR) brake has been introduced, aiming to enhance both the efficiency and safety of vehicle safety systems, thereby accelerating the commercial adoption of such brakes in the automotive industry. This innovative brake uses a hybrid operational mode, replacing the conventional rotary motion with a unique recessive structure to enhance the braking performance. In the non-braking state, the design maintains the fluidity of the MR fluid, while in the braking state, it leverages the brake disc's recessive movement. Additionally, the study incorporates a temperature compensation mechanism to mitigate potential performance variations due to temperature changes. A three-dimensional static magnetic field analysis confirmed the magnetic circuit design's effectiveness and the suitability of the selected parameters and materials. The simulation showed that the brake's average magnetic field intensity rose by 145.26% when increasing the current from 1A to 4A, achieving a maximum braking torque of 51.4 Nm.
Keywords: Brake-by-wire system, reverse extrusion, magnetorheological brake, temperature compensation, electromagnetic field simulation